Distribution and Community Characteristics of Staging Shorebirds on the Northern Coast of Alaska - Taylor, Audrey R.; Lanctot, Richard B.; Powell, Abby N.; Huettmann, Falk; Nigro, Debora A.; Kendall, Steven J. (ARCTIC, 2010)
Avian studies conducted in the 1970s on Alaska’s Arctic Coastal Plain (ACP) indicated that coastal littoral habitats are important to Arctic-breeding shorebirds for staging prior to fall migration. However, relatively little recent, broad-scale, or quantitative information exists on shorebird use of staging areas in this region. To locate possible shorebird concentration areas in the littoral zone of the ACP, we conducted aerial surveys from the southwest end of Kasegaluk Lagoon on the Chukchi Sea to Demarcation Point on the Beaufort Sea during the summers of 2005–07. These surveys identified persistent within- and between-year concentrations of staging shorebirds at Peard Bay, Point Barrow/Elson Lagoon, Cape Simpson, and Smith Bay to Cape Halkett. Among river deltas in the Beaufort Sea, the Sagavanirktok and Kongakut deltas had large concentrations of staging shorebirds. We also collected data on shorebird community characteristics, staging phenology, and habitat use in 2005 and 2006 by conducting land-based surveys at six camps: Kasegaluk Lagoon, Peard Bay, Point Barrow/Elson Lagoon, Colville Delta, Sagavanirktok Delta, and Okpilak Delta. The shorebird community was more even and diverse (evenness E and Shannon Weiner H’) along the Beaufort Sea compared to the Chukchi Sea and in 2005 versus 2006. Staging phenology varied by species and location and differed for several species from that reported in previous studies. Our results suggest the existence of three foraging habitat guilds among the shorebird species observed in this study: gravel beach, mudflat, and salt marsh/pond edge. A comparison to data collected in the mid-1970s suggests that these foraging associations are conserved through time. Results from this research will be useful to land managers for monitoring the effects of changing environmental conditions and human activity on shorebirds and their habitats in Arctic Alaska. Des études aviaires réalisées dans les années 1970 sur la plaine côtière de l’Arctique en Alaska ont permis de constater que ...